Small business management launching & growing entrepreneurial ventures - Longenecker, Justin Gooderl (Delmar, Cengage Learning, 2014)
Provides the practical concepts, entrepreneurial insights, and comprehensive resources that you'll find essential both now and throughout your management future. This title delivers coverage of the fundamentals of business management as it teaches you not only how to start a business, but also how to manage, grow, and harvest a business.